2014
DOI: 10.1038/sj.bdj.2014.249
|View full text |Cite
|
Sign up to set email alerts
|

An audit of cavity and crown preparations and two direct restorations carried out by foundation dentists in the Oxford and Wessex Deaneries

Abstract: It is likely that many foundation dentists (FDs) will have completed only minimal amounts of restorative dentistry for a number of months immediately prior to commencing work as FDs. Thus this audit aimed to assess the performance of the FDs when they carried out a number of simulated clinical exercises: amalgam cavities and restoration; Class IV resin composite restorations; and full crown preparations for metal-ceramic restorations. A total of 67 FDs completed the assessments and some results did indicate a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
1
6
1
Order By: Relevance
“…In an ideal investigation, two or more examiners might have been used, but this was not possible in the present study. However, the reliability of the examiner in the present study had been demonstrated in the previous work 4 .…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…In an ideal investigation, two or more examiners might have been used, but this was not possible in the present study. However, the reliability of the examiner in the present study had been demonstrated in the previous work 4 .…”
Section: Discussionsupporting
confidence: 62%
“…As a result, Jokstad and Mjor, in 1987 10 , defined criteria for external outline, external cavity definition, margin roughness and internal cavity definition, with five different scale points. It was considered that that system was too complex for the present study, hence the development of the present, simplified, scoring system, which has been considered to work satisfactorily in the present study and in previous work 4 .…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations